PENGARUH INTERVENSI CORE STABILITY EXERCISE TERHADAP KESEIMBANGAN DINAMIS PEMAIN BASKET DI SMP NEGERI 152 JAKARTA TAHUN 2023 - Magdalena, Maria; Lina, Ratu Karel; Trioclarise, Rovika (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background: Currently, the development of basketball in Indonesia, especially in Jakarta, has increased drastically. However, there are still some basketball players who cannot handle basic techniques well. They just play without understanding the basic techniques of basketball well. At a young age, the risk of falling can be affected by a low level of balance, Core Stability Exercise is a major component to improve the efficiency of sports movements.Objective: To know the effect of Core Stability Exercise intervention on dynamic balance in basketball players of SMP Negeri 152 Jakarta. Method: This study used Pre-Experimental research with two group pretest - postest which was conducted at SMP Negeri 152 Jakarta. Determination of the sample using purposive sampling and obtained 10 samples selected based on the inclusion criteria. Dynamic balance measurements were taken using the Y Balance Test at the beginning and end of the intervention for 3 weeks. Results: Paired T-test Core Stability Exercise before and after intervention obtained p value = 0.000 (p < 0.05). Conclusion: There is an effect of Core Stability Exercise intervention on dynamic balance in basketball players of SMP Negeri 152 Jakarta.